Rhabdomyosarcomas arising from striated muscles in elderly dogs: pathological features of 4 cases - BRELLOU (Γ.Δ. ΜΠΡΕΛΛΟΥ) G. D.; PSYCHAS (Β. ΨΥΧΑΣ) V.; VLEMMAS (Ι. ΒΛΕΜΜΑΣ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Primary rhabdomyosarcomas are rare in dogs. Based on their classification, embryonal rhabdomyosarcoma is the most common, while alveolar and especially pleomorphic types occur less often. Four cases diagnosed as primary canine rhabdomyosarcomas of striated muscles were retrieved from our files. All the animals were cross-breeds, aged over 8 years. Two of them had died after developing disseminated intravascular coagulation and gastric ulcer, respectively, and two others were euthanized. Of those two, one had been admitted with neurological and cardiovascular symptoms and one with disseminated intravascular coagulation. Necropsy was performed and tissue samples were collected for histological and immunohistochemical examination. The first case was diagnosed as mixed rhabdomyosarcoma, pleomorphic type in the heart and the diaphragm and alveolar type in the lungs and the spleen. The three other cases were of alveolar type. One showed primary cardiac and oesophageal origin, with metastases in the skeletal muscles and non striated muscle tissues, one had primary cardiac, with mitral valve involvement, and skeletal muscle origin, with metastases in extra striated muscle tissues and one showed only skeletal muscle localization. Immunohistochemical examination revealed myoglobin and α-sarcomeric actin in tumour cells.